Active methodological strategy "teamwork" to the development of the competence "quantity problem solving" in the area of mathematics in elementary school - Diaz Zea, Katty Magnolia (2022)
The study aims to apply the active methodological strategy "Teamwork" to improve the development of the competence "solving quantity problems" in students of the Fourth Grade of Primary Education in the area of Mathematics at the Emblematic Educational Institution "Simón Bolívar” Of Moquegua in 2019. As scopes we have that it was possible to diagnose the factor that causes the low academic level in students, then describe the way in which the active methodological strategy "Teamwork" is applied and in this way analyze the elation ship that exists between the two variables, concluding with demonstrating its effectiveness. This research is characterized by having used the application-type methodology, with a quasi-experimental design of two non-randomized groups. The population consisted of 79 students, obtaining as a result that in section "A" as in "C" a "level of achievement" of 17% was obtained, and in the "process level" a 14% was obtained. in section "A" and 4% in section "C" demonstrating significant efficacy in the two experimental groups. The significant conclusion is that "achievement" was obtained in section "A" of 24% and in "C" of 28% and in section "Process" it was obtained in section "A" of 20% and in the "C" of 7%, which shows a substantial improvement.